Defected ground structure based compact microstrip lowpass filter with wide stopband - Sahu B.; Singh S.; Meshram M.K.; Singh S.P. (My University, 2025)
In this paper, a compact lowpass filter (LPF) with wide stopband is reported which uses four non-uniform cascaded defected ground structure (DGS) units along with a 50 Ω microstrip line. Each DGS unit is formed by combining three isosceles U-shaped DGSs and provides three attenuation poles. The proposed LPF has size of 14.44 mm × 3.4 mm, 3-dB cut-off frequency of 14.2 GHz, and greater than 40 dB and 22 dB stopband rejection upto 21.8 GHz and 30 GHz respectively. The proposed LPF is fabricated and experimentally tested. The experimental results are nearly in agreement with corresponding numerical simulation results. © 2017 IEEE.